Understanding Ambiguous Meaning and Sound Through The Learning Materials of Micro linguistics - Utari, Aisyah Ririn Perwikasih (Sebelas Maret University, 2016)
Since language is universal, its linguistic components also can be learnt universally. Ambiguity happens to any kind of language. It can be both written and spoken. Written words, phrases or sentences can be analyzed both lexically and structurally. Spoken ones can be analyzed through its lexical, structural, and sound meaning. Ambiguous meaning in written language can be solved through some contextual analysis, while in spoken language, both contextual analysis and sound focus and clearness are needed. Microlinguistics provides the basic language features which cover phonetics, phonology, morphology, syntax, and semantics. Commonly, ambiguity deals with meaning and sound. If the sound is unclear, the meaning will be unclear as well. Phonetics and phonology can solve the studentsâ problems of having ambiguous meaning because of sound. Syntax and semantics can solve the wrong interpretation of particular language especially English, both lexically and structurally. In the learning activity, students are facilitated with materials which are presented through power point of the features they need to know in microlinguistics. There is also some phonetics drilling of sound producing until they can master how to pronounce English sounds well. For the practice of analyzing ambiguity through its structural components, the students should use syntactic analysis to break the phrase or sentences until the correct meaning is found. Analysis of ambiguous meaning and sound can give the new knowledge for students to be familiar with ambiguity in daily communication. Students also can respond ambiguity scientifically through its linguistic features.